Design of Vehicle-infrastructure Cooperation System for Autonomous-rail Rapid Tram Based on the Communication Technology of C-V2X - RONG Shaohua; WANG Songhao; OUYANG Botao (Kongzhi Yu Xinxi Jishu)
In order to reduce the influence of mixed traffic on urban roads and bad weather environment on the safety and operation efficiency of autonomous-rail rapid tram, based on the communication technology of C-V2X, this paper proposes a technical scheme of vehicle-infrastructure cooperation, and vehicle-infrastructure cooperation system for autonomous-rail rapid tram is designed. Firstly, the requirements and characteristics of autonomous-rail rapid transit(ART) in operation are analyzed, and the overall architecture and equipment deployment scheme vehicle-infrastructure cooperation system of autonomous-rail rapid tram are designed; then, the V2X scene which accords with the running characteristics of autonomous-rail rapid tram is derived and expanded, and through the functional design and planning of C-V2X application service platform, the safety warning of autonomous-rail rapid under severe weather conditions such as fog and rainstorm, monitoring and warning of abnormal traffic events under mixed traffic conditions, etc. are realized. The technical scheme of vehicle-infrastructure cooperation based on C-V2X can provide guidance and reference for the construction of intelligent road facilities of ART.